Fabrication of multifunctional mucoadhesive buccal patch for drug delivery applications. Issue 12 (30th June 2021) - Rohani Shirvan, Anahita; Hemmatinejad, Nahid; Bahrami, S. Hajir; Bashari, Azadeh
Abstract: Mucoadhesive buccal patch is a promising dosage form for a successful oral drug delivery, which provides unique advantages for various applications such as treatment of periodontal disease and postdental surgery disorders. The aim of this study is to synthesize a novel multifunctional mucoadhesive buccal patch in a multilayer reservoir design for therapeutic applications. The patches were fabricated through simultaneous electrospinning of chitosan/poly(vinylalcohol) (PVA)/ibuprofen and electrospraying of phenylalanine amino acid nanotubes (PhNTs) containing metronidazole into the electrospun mats through a layer‐by‐layer process. An electrospun poly(caprolactone) (PCL) was used as an impermeable backing layer to protect the mucoadhesive component from tongue movement and drug loss. Buccal patches were characterized using scanning electron microscopy (SEM) and field emission scanning electron microscopy (FESEM) and also evaluated in terms of physicomechanical parameters such as pH, weight, thickness, tensile strength, folding endurance, and mucoadhesive properties. The swelling index of the patches was examined with respect to the PVA/chitosan ratio. The effect of genipin addition to the electrospinning solution was also studied on mucoadhesive and swelling properties. The cell viability of buccal patches was assessed by methylthiazolydiphenyl‐tetrazolium bromide test on L929 fibroblast cell line. The patch with an optimal amount of mucoadhesive polymers (PVA/chitosan 80:20) and crosslinking agent (0.05 g) indicated an ideal hemostatic activity along with antibacterial properties against Streptococcus mutans bacteria. The synthesized multifunctional mucoadhesive patch with a novel composition and design has a great potential for oral therapeutic applications.